The Influence of Vibration on Friction: A Contact-Mechanical Perspective - Popov, Mikhail (Frontiers in Mechanical Engineering, 2020)
A unified model for active control of static and sliding friction by normal, tangential and transverse oscillations is discussed, building on a series of past publications. The model in question is quasi-static, uses Amontons friction and takes into account contact stiffness in both normal and tangential directions. This makes the model fully macroscopic, which stands in contrast to Prandtl-Tomlinson-derived microscopic models that seem to be the currently preferred explanation for the influence of vibration on friction. While many technical details and numerical simulations based on our model have already appeared in a series of publications, here we attempt to give a high-level overview and discuss the main properties of friction under oscillation as generally as possible, while making a minimum of assumptions.